Analisis Produktivitas Penjahit dengan Menggunakan Metode Work Sampling - Raodah, Raodah; Aqsha, Ismail; Husda, Baso Riadi; Ramdhani, Irin; Erniyani, Erniyani (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Work sampling is a work measurement method to determine the proportion of time spent in various work system activities, either by humans, machines, or processes. This study identifies the proportion of productive and non-productive activities and determines the standard time as a basis for improving work effectiveness, especially in the activities of sewing operators. The work sampling method was used with 69 random observations over eight working hours of one operator. Analysis involved statistical calculation of proportion distribution, rating factor, allowance, as well as cycle, normal, and standard time. The results showed that 81,16% of the activities performed were productive with a standardized time of 179,79 minutes per work cycle. The idle time level was recorded at 18,84%. This finding indicates that the observed work system still leaves potential for improvement in unproductive time. The conclusion of this study emphasizes the importance of implementing work sampling as a method to design data-driven work system improvements, in order to increase overall work productivity and efficiency.